DISTRIBUTION OF BALI STARLING (Leucopsar rothschildi) IN NUSA PENIDA ISLAND - Sudaryanto, FX.; Subagja, Jusup; Pudyatmoko, Satyawan; Djohan, Cut Sugandawaty (SIMBIOSIS, 2018)
Bali Starling ( Leucopsar rothschildi Stresemann, 1912) is endemic bird to the Bali Island. Since 1966, Bali Starling has been categoried as Critically Endangered by the IUCN Red List of Threatened Species, and the Indonesian Government Regulation No. 7 of 1999 on Preservation of Fauna and Flora. Conservation of Bali Starling has been done in the Bali Barat National Park, but has not succeeded yet. Therefore, starting in 2006 the conservation of the Bali Starling is also done in the Nusa Penida Islands, Klungkung Regency. To examine the successful of conservation of Bali Starling in Nusa Penida Islands, need the studies as follows: How is the distribution of Bali Starling? This research aims to study the success of conservation of Bali Starling in Nusa Penida Island. Specifically, the purpose of this research were to study distribution of Bali Starling. Materials and methods used in this research was known from questioned to the people in the area, and also conducted exploration. Distribution of Bali Starling in 2006 was only in three locations, and being expanded in 2015 there were at least in 12 locations. Keywords:     Bali Starling, Leucopsar rothschildi, Nusa Penida I sland, Bali,distribution